2016
DOI: 10.1111/bjop.12205
|View full text |Cite
|
Sign up to set email alerts
|

It's immoral, but I'd do it! Psychopathy traits affect decision‐making in sacrificial dilemmas and in everyday moral situations

Abstract: This research investigated whether emotional hyporeactivity affects moral judgements and choices of action in sacrificial moral dilemmas and in everyday moral conflict situations in which harm to other's welfare is differentially involved. Twenty-six participants with high trait psychopathy (HP) and 25 with low trait psychopathy (LP) were selected based on the primary psychopathy scale of the Levenson Self-Report Psychopathy Scale. HP participants were more likely to sacrifice one person to save others in sacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 83 publications
9
65
2
1
Order By: Relevance
“…Furthermore, individuals with emotional hyporeactivity (e.g., participants with high psychopathy traits, or vmPFC impairments) show a higher endorsement of utilitarian options as compared to control participants (e.g., Koenigs et al, 2007, 2012; Moretto et al, 2010; Pletti et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individuals with emotional hyporeactivity (e.g., participants with high psychopathy traits, or vmPFC impairments) show a higher endorsement of utilitarian options as compared to control participants (e.g., Koenigs et al, 2007, 2012; Moretto et al, 2010; Pletti et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Yet, they do not appear to differ from individuals with low levels of these traits in relation to their moral judgment ability, i.e. the ability to judge whether an action is immoral or not3456789 (though see refs 10, 11 for exceptions). However, they do report less difficulty in making decisions when faced with moral dilemmas679 and present diminished neural responses in the amygdala and other regions typically associated with affective processing when they perform moral judgment tasks4581213.…”
mentioning
confidence: 99%
“…the ability to judge whether an action is immoral or not3456789 (though see refs 10, 11 for exceptions). However, they do report less difficulty in making decisions when faced with moral dilemmas679 and present diminished neural responses in the amygdala and other regions typically associated with affective processing when they perform moral judgment tasks4581213. Atypical moral behaviour in these individuals seems to stem not from an inability to compute moral judgments, but rather from a disruption of the affective and motivational components of moral processing that may be important for adjusting one’s behaviour so as not to harm others31415.…”
mentioning
confidence: 99%
“…Studies using other moral reasoning measures, however, suggest a different pattern of effects. Studies of emerging adults have indicated that affective psychopathy is associated with utilitarian responses but not acceptability ratings in response to moral scenarios (Pletti et al, 2017; Tassy, Deruelle, Mancini, Leistedt, & Wicker, 2013). Another study of college students showed that aggression partially mediated the relation between psychopathic traits and utilitarian moral reasoning (Balash & Falkenbach, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using emerging adult samples have shown mixed findings, but still provide evidence that the personality factor of psychopathy is associated with both proactive and reactive aggression, whereas the lifestyle factor of psychopathy is more strongly associated with merely reactive aggression (Falkenbach, Poythress, & Creevy, 2008;Ostrov & Houston, 2008;Reidy, Zeichner, Miller, & Martinez, 2007). In addition, previous literature has demonstrated a unique effect of the personality factor on morally relevant decisions and behaviors in young and middle-aged adults (Coyne & Thomas, 2008;Pletti, Lotto, Buodo, & Sarlo, 2017;Seara-Cardoso, Neumann, Roiser, McCrory, & Viding, 2012). We thus chose to solely focus on the personality factor of psychopathy, as the emotional desensitization inherent in the personality factor is a stable internal characteristic that may more directly be related to latent cognitive structures (e.g., worldviews) than a pattern of erratic behavior.…”
Section: Aggression Moral Reasoning and Social Cognitionmentioning
confidence: 99%